Cadmium sulfide (CdS) nanoparticles and Cd2+ accumulated by Portulaca oleracea L. using a hydroponic system: Constructed wetland perspective - Hameed Ullah; Yanqing Sheng (Ecotoxicology and Environmental Safety)
To identify cadmium sulfide nanoparticles (CdS NPs) and Cd hyperaccumulators for Cd-contaminated waters. A potential species of constructed wetland plants (P. oleracea) was examined for their CdS NPs and Cd ions tolerance and accumulation. This study evaluated the P. oleracea life traits response, Cd accumulation, bioaccumulation factor (BCF), and translocation factor (TF) to assess their abilities to absorb and accumulate Cd. P. oleracea demonstrates high tolerance to both CdS NPs and Cd stress, with no significant effects observed on biomass, leaf color, plant height, or root length. High accumulation of Cd was noted in plant tissues, with higher Cd in the roots than in the stems and leaves. The Cd levels in plants subjected to CdS NPs were higher than those in the Cd treatment group. CdS NPs aggregates were identified within the plant cells in root and shoot tissues using transmission electron microscopy (TEM). The BCF values ranged from 6.96 to 548.10 for the Cd treatment and 12.91–499.66 for CdS NPs, indicating the ability of P. oleracea to accumulate Cd and NPs. Additionally, TF values for Cd at 0.05 and 0.1 mg/L were above 1, showing effective translocation capability. The findings suggest that P. oleracea demonstrates significant potential as a Cd-hyperaccumulator, exhibiting a robust ability to extract Cd and CdS NPs from contaminated waters. It is a feasible plant in a constructed wetland for Cd removal.